Generation of an integration-free induced pluripotent stem cell line, FJMUUHi002-A, from a Rett syndrome patient with a heterozygous mutation p. R133C in MeCP2 - Guo, Yu; Li, Jiaqi; Xie, Wenyi; Huang, Huaping; Li, Jin-Jing; Lin, Wanhui; Lu, Ying-Qian (Stem cell research, 2024)
The human iPS cell line, hiPS-RTT (FJMUi002-A), is derived from peripheral blood mononuclear cells (PBMCs) from a 12-year-old female RTT patient carrying a heterozygous p. R133C (c.397C > T) mutation in the MeCP2 gene. The hiPS-RTT cell line was generated by non-integrative reprogramming vectors encoding OCT3/4, SOX2, KLF4, and c-MYC and was free of genomically integrated reprogramming genes. The hiPS-RTT cell line had a normal karyotype, expressed pluripotency markers, and had capacity to form three germ layers in vitro and in vivo, which offering a useful resource to study the pathogenesis and treatment strategies of RTT.